Cultivating Self-Acceptance: A Study on the Effectiveness of Acceptance and Commitment Therapy (ACT) in the ODHIV Community - Sutansyah, Sani; Wibhowo, Christin; Siswanto, Siswanto (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
People with HIV/AIDS (PWHA), particularly from the Men who have Sex with Men (MSM) group, often face double stigma which negatively impacts their self-acceptance. Low self-acceptance can hinder treatment adherence and quality of life. Acceptance and Commitment Therapy (ACT) is a psychotherapeutic approach hypothesized to improve self-acceptance. This study aimed to examine the effectiveness of Acceptance and Commitment Therapy (ACT) intervention in improving self-acceptance among PWHA from the MSM group. The study used a one group pre-test post-test design. Participants were five MSM PWHA selected by purposive sampling. The ACT intervention was delivered in six individual sessions. The measurement instrument used was the Unconditional Self-Acceptance Questionnaire (USAQ). Data were analyzed statistically using the Wilcoxon Signed Rank Test and supported by qualitative analysis from observations and interviews. The statistical test results showed a significant increase (Z = -2.032; p = 0.042) between the pre-test scores (Mean = 33.8; low category) and post-test scores (Mean = 57.2; moderate category). Qualitatively, participants reported reduced anxiety and negative thoughts, as well as an increased ability to accept their condition and openness to socialize. Although significant, no participant reached a